SISTEM INFORMASI PENGOLAHAN DATA PASIEN PADA PUSKESMAS TENAM MUARA BULIAN: Puskesmas;Public Health;Information Services. - Louis, Ahmad; Reka Silvia, Febi (JURNAL AKADEMIKA, 2021)
Pusat Kesehatan Masyarakat (Puskesmas) is a provider of public health services to always provide fast, precise and accurate health services. Pusat Kesehatan Masyarakat (Puskesmas) have the main function to provide medical services in the form of perfect care and treatment to the community Data processing is a function of administrative activities used by agencies or offices to provide information services to organizations to deal with many managements. This health center is the object of this research, because at this time the patient data processing system is still manual, this is due to the absence of an integrated data processing system and mechanism and the limited facilities and infrastructure of information services that are produced not as expected. The author tries to find a solution to the problem in processing this data by implementing a computer-based data processing system